Building Identity For New Bands: A Community Engagement Initiative For Rock Band "RedFlag" In The Alternative Rock Genre - Sabeth Uttara Sihotang; Muhammad Faishal Nashif; Rovaldo Ferdiansyah; Adam Muhammad Ramadhan; Muhammad Alifa Rizqy Prawira (ABDIMAS Jurnal Pengabdian Kepada Masyarakat, 2024)
The Community Service Program (CSP) aims to elevate RedFlag, an emerging alternative rock band, within the Indonesian rock scene. It focuses on brand development, visibility, performance opportunities, industry networking, music production, and community engagement. RedFlag has shown potential with their debut single “Bottle Down” and collaborations with CRYSTAGELLA, enhancing their industry connections. However, challenges include stagnant social media growth and recent lineup changes. CSP's approach includes building a strong brand identity, boosting online presence through targeted social media, and securing performance slots at venues and festivals. The program also facilitates networking with industry professionals, offers mentorship, and improves music production quality while promoting community engagement through local events. Continuous monitoring and feedback will ensure the effectiveness of these strategies, aiming to help RedFlag succeed in the competitive Indonesian music industry.